Guideline updates for definition, diagnosis and management of hepatorenal syndrome - Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2020)
Hepatorenal syndrome (HRS) is a unique form of acute kidney injury (AKI) developing in patients with end‐stage liver disease. AKI is a frequent complication in advanced cirrhosis patients which is associated with increased hospital admissions and decreased survival. The definition of AKI in cirrhosis has been recently modified and the new diagnostic criteria are based on small changes in serum creatinine with respect to previous values, occurring within a short period of time. Systemic circulatory dysfunction and marked kidney vasoconstriction play a key role in the development of HRS. The modification of the AKI definition has also led to a change in the diagnostic criteria of HRS. The new diagnostic criteria are based on AKI stages and there is no need to reach a specific serum creatinine threshold. The use of the new HRS definition may lead to an earlier identification of renal impairment and better prognostic stratification. According to these new criteria, treatment with vasoconstrictors and albumin for the management of HRS will be started at lower serum creatinine values, with expected higher response rates. There are consistent data showing that some urine biomarkers, particularly NGAL (neutrophil gelatinase‐associated lipocalin), may be useful in daily clinical practice for the differential diagnosis of the cause of AKI in cirrhosis. Various HRS treatment regimens are available worldwide and all are designed to increase the mean arterial pressure by increasing the central blood volume and decreasing splanchnic vasodilation, and to serve as bridge to liver transplantation.